Gestational and congenital syphilis in the southeast region: epidemiological analysis - Dias, Fernanda Rodrigues; Monteiro , Denise Leite Maia; Morgado, Flávio Eduardo Frony; Dorovni, Rafaela Barbosa Peixoto; Corrêa, Julia Bueno dos Reis; Mazzaro, Filipe Braz Barbosa Maidecchi; Ávila, Marcela Ignacchiti Lacerda (Brazilian Journal of Sexually Transmitted Diseases, 2026)
Introduction: Brazilian public health faces constant challenges to meet demographic and social changes, and despite current policies, rates of sexually transmitted infections, such as syphilis, especially in pregnant women and newborns, are still high. Primary Health Care is recognized as the best way to act on maternal and child health, with prenatal care being essential for the diagnosis and follow-up of pregnant women. Objective: To analyze the social and epidemiological profile of pregnant women and newborns with syphilis in the Southeast region of Brazil between 2019 and 2022. Methods: This is a descriptive and cross-sectional research, with data from Brazilian Epidemiological Indicators and the 2023 Epidemiological Bulletin of the Brazilian Ministry of Health. Results: According to the results, the Southeast region concentrates almost 50% of the cases of gestational and congenital syphilis in Brazil. Although many pregnant women receive prenatal care and are diagnosed in the first trimester, a significant proportion still receive incomplete treatment, which negatively affects the newborn. Conclusion: Syphilis continues to be a serious public health issue, especially in the Southeast, with alarming growth rates. Therefore, it is essential to implement public policies that improve the quality of prenatal care, ensuring continuous follow-up during pregnancy and in the postpartum period for effective diagnosis and treatment of syphilis.